2007
DOI: 10.1007/s11306-006-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

An NMR- and MS-based metabonomic investigation of saliva metabolic changes in feline odontoclastic resorptive lesions (FORL)-diseased cats

Abstract: The feline odontoclastic resorptive lesion (FORL) is a common oral problem in cats. The disease has increased steadily since the domestication of cats and etiology of this disease has not been fully determined although several theories have been proposed. Feeding practices, vaccination, and neutering programs have all been suspected to be associated with FORL. The aim of the current study is to assess the feasibility of metabonomics to detect at an early stage the onset of the disease. The diagnostic biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The samples were thawed at room temperature and centrifuged (14 000 rpm for 30 min at 4 °C) to remove cells, mucus, and macromolecules. 540 μL of supernatant was then taken and immediately added to 60 μL of phosphate buffer (composition: 0.2 M Na 2 HPO 4 , 0.2 M NaH 2 PO 4 , 30 mM NaN 3 , and 10 mM TSP (sodium trimethylsilyl [2,2,3,3- 2 H 4 ] propionate) in 100% 2 H 2 O; pH 7.4) . NaN 3 was also added as a preservative to ensure that metabolites were not generated or consumed due to bacteria present in the saliva during the time of preparation of the samples or of the acquisition of NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were thawed at room temperature and centrifuged (14 000 rpm for 30 min at 4 °C) to remove cells, mucus, and macromolecules. 540 μL of supernatant was then taken and immediately added to 60 μL of phosphate buffer (composition: 0.2 M Na 2 HPO 4 , 0.2 M NaH 2 PO 4 , 30 mM NaN 3 , and 10 mM TSP (sodium trimethylsilyl [2,2,3,3- 2 H 4 ] propionate) in 100% 2 H 2 O; pH 7.4) . NaN 3 was also added as a preservative to ensure that metabolites were not generated or consumed due to bacteria present in the saliva during the time of preparation of the samples or of the acquisition of NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolomics, the term describing the global analysis of metabolites, has emerged as a powerful approach used in many disciplines to study how a stimulus causes perturbations in the metabolite profile. Nuclear magnetic resonance (NMR) is one of the principal analytical technique for metabolomic purposes, , and blood and urine are the biofluids most frequently studied in these investigations. , In contrast, the use of saliva in metabolomic studies are rare; , however, recently a comprehensive investigation of the salivary metabolome was reported . This is despite the fact that the use of saliva has an important advantage, as it is easily accessible and can be sampled noninvasively without the introduction of stress or pain.…”
mentioning
confidence: 99%
“…Ramadan et al . 41 observed that there are increased levels of acetate, lactate, propionate, isovalerate, tryptamine and phenylalanine, indicating changes in oral microflora of cats infected with feline odontoclastic resorptive lesion, suggesting that it is possible to predict feline odontoclastic resorptive lesion disease at early stage by monitoring metabolite profiles in saliva samples. Williams et al .…”
Section: Literature Reviewmentioning
confidence: 99%